Self-adaptive Janus supramolecular hydrogel, preparation method and application of self-adaptive Janus supramolecular hydrogel as wet tissue surface adhesive
By using Janus hydrogel in dura defect repair, it consists of an adhesion surface and an anti-adhesion surface, and forms a firm interface combination through strong ion interaction, the problems of low wet adhesion strength, high swelling rate and tissue adhesion in dura defect repair are solved, and high wet adhesion strength, low swelling rate and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202510124976.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-27
AI Technical Summary
In the repair of dural defects, existing hydrogel adhesive materials have problems such as low wet adhesion strength, high swelling rate, unstable interface bonding and tissue adhesion, which is difficult to meet clinical needs.
A Janus hydrogel is used, which consists of an adhesive surface and an anti-adhesive surface. The adhesive surface is prepared from raw materials including the first monomer, the second monomer, N-isopropylacrylamide and a photoinitiator. The anti-adhesive surface is prepared from raw materials including the third monomer and the photoinitiator. It forms a firm interface bond through strong ion interaction.
It achieves high humidity adhesion strength, low swelling rate, good mechanical properties and anti-tissue adhesion effect, meeting the high standard needs of dura defect repair.
Smart Images

Figure CN119552318A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymers, and in particular relates to an adaptive Janus supramolecular hydrogel, a preparation method and application thereof as a wet tissue surface adhesive. Background Art
[0002] Cerebrospinal fluid leakage caused by dural defect is a common complication in spinal and neurosurgery. It has a high incidence rate and a high degree of harm, and may cause paralysis or even death. It is an important challenge in clinical practice. The existing clinical strategy is mainly through suturing, but surgical suturing is not only technically difficult, has poor closure effect, and is prone to cause needle leakage, but also causes problems such as tissue adhesion. The adhesives currently used on the market, such as fibrin-based and cyanoacrylate, have problems such as poor adhesion and poor safety. Existing patches such as bovine pericardial patches, animal collagen, polytetrafluoroethylene and polylactic acid need to be sutured or sealed with glue through surgery. They have problems such as unstable wet adhesion, compression of spinal nerves after swelling, poor matching with tissue mechanical properties and tissue adhesion, which cannot meet the high standard requirements for repairing dural defects in spinal and neurosurgery. The ideal dural repair material should have stable wet adhesion, mechanical properties matching with tissues, controllable mass and volume, and have the functions of promoting repair and preventing tissue adhesion.
[0003] Hydrogel materials have been applied in the above-mentioned fields in the prior art, but the following analysis shows that there is still a lack of biomedical materials that have structural characteristics similar to extracellular matrix, excellent biocompatibility, adjustable and reversible adhesion strength, low swelling rate, and can both stably adhere to wet tissue surfaces and prevent tissue adhesion.
[0004] For example, patent document CN 113577370 A discloses a method of using acrylamide as a monomer, dissolving a crosslinker, a photoinitiator and a monomer in water, and initiating polymerization by ultraviolet light to obtain an anti-adhesion layer of a Janus hydrogel; then using acrylic acid as a monomer, dissolving it in water with a crosslinker, a photoinitiator and lithium terephthalate, and pouring it on the surface of the anti-adhesion layer, and initiating polymerization by ultraviolet light to obtain a Janus hydrogel adhesive. Since it uses a crosslinker, the toxicity of the hydrogel material is increased, and it is prepared by pouring a prepolymer liquid on the surface of the hydrogel and then performing photopolymerization. The prepared hydrogel is a composite type, not an integrated structural design, and there are problems such as poor composite interface strength and poor wet adhesion. In addition, it mainly uses a hydrophilic monomer acrylic acid, and the prepared hydrogel has a high swelling rate.
[0005] Patent document CN 117414464 A discloses a method of copolymerizing sodium hyaluronate acylated with sulfobetaine zwitterionic monomers under ultraviolet light, and then soaking in a photoinitiator α Ketoglutaric acid, and finally acrylic acid and N The aqueous solution of hydroxysuccinimide acrylate monomer is coated on the hydrogel and then polymerized under ultraviolet light to obtain the Janus hydrogel adhesive. However, due to the surface coating strategy, the prepared Janus hydrogel is also a non-integrated structure, and the hydrogel has low strength (~0.1Mpa), high swelling rate, and poor wet adhesion, which makes it difficult to meet the clinical needs in the field of dura mater defects.
[0006] Patent document CN 118530410 A uses hexadecyltrimethylammonium bromide (CTAB) to emulsify hydrophilic monomer acrylic acid and hydrophobic monomer lauryl methacrylate (LMA), then adds phenylboronic acid groups and quaternary ammonium salt groups to functionalize polyphosphazene and natural polyphenols, and finally uses photoinitiator to polymerize to obtain Janus hydrogel. The emulsifier used is easy to bring toxicity, and the introduction of natural polyphenols has the effect of inhibiting polymerization, which easily leads to insufficient polymerization of monomers and increases toxicity, making it difficult to be used in vivo. At the same time, the mechanical properties and wet adhesion strength are still insufficient.
[0007] In summary, the existing hydrogel adhesive materials not only have low wet adhesion strength, but also absorb water and swell. In addition, the synthesis of this type of Janus hydrogel is mostly through simple casting and compounding, and it is not an integrated structure. There are problems such as unstable interface bonding between the adhesive layer and the anti-adhesion layer, easy shedding in the body fluid environment, and tissue adhesion. It is suitable for applications in fields such as skin wound healing, but difficult to apply to the field of dura mater defect repair. Summary of the invention
[0008] In order to improve the above technical problems, the present invention provides a Janus hydrogel having an adhesive surface and an anti-adhesive surface; The adhesive surface is prepared from raw materials including a first monomer, a second monomer, N-isopropylacrylamide (NIPAM) and a photoinitiator; The anti-adhesion surface is prepared from raw materials including a third monomer and a photoinitiator; The first monomer is one or more selected from polyethyleneimine (PEI), hyperbranched polyethyleneimine, tetraethylenepentamine, triethylenetetramine, polylysine, poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA), polyethyleneamine and polypropyleneimine; The second monomer is selected from one or more of acrylic acid (AA), methacrylic acid, 2-acrylamide-2-methylpropanesulfonic acid (AMPS), itaconic acid, vinyl phosphate, and hydroxyethyl phosphate methacrylate; The third monomer is a zwitterionic monomer; Preferably, the raw materials used to prepare the adhesive surface and the anti-adhesive surface do not contain toxic additives, such as cross-linking agents and / or emulsifiers.
[0009] According to an embodiment of the present invention, the zwitterionic monomer includes but is not limited to one or more of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (DMAPS), 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA) and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate (CBAA).
[0010] According to an embodiment of the present invention, the molecular weight of the first monomer is 30,000-100,000, such as 40,000-80,000, 50,000-70,000.
[0011] According to an embodiment of the present invention, the Janus hydrogel has an integrated structure, that is, the adhesive surface and the anti-adhesive surface form an interpenetrating network structure, and generate a strong interface bond through strong ionic interaction.
[0012] According to an embodiment of the present invention, the photoinitiator is selected from α One or more of ketoglutaric acid, 2,2-diethoxyacetophenone (DEAP) and lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0013] According to an exemplary embodiment of the present invention, the adhesive surface is prepared from raw materials including polyethyleneimine / hyperbranched polyethyleneimine, acrylic acid / methacrylic acid, N-isopropylacrylamide and a photoinitiator; The anti-adhesive surface is prepared from raw materials of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and a photoinitiator.
[0014] The present invention also provides a method for preparing a Janus hydrogel, the method comprising the following steps: (1) preparing an adhesive surface from raw materials including a first monomer, a second monomer, N-isopropylacrylamide (NIPAM) and a photoinitiator; (2) on one side of the adhesive surface, using a raw material including a third monomer and a photoinitiator to prepare an anti-adhesive surface to obtain the Janus hydrogel; The first monomer, the second monomer, the third monomer and the photoinitiator are all as defined above.
[0015] According to an embodiment of the present invention, the molar ratio of the first monomer (calculated by molar amount of structural units), the second monomer, N-isopropylacrylamide and the third monomer is 1: (0.8~2): (0.05~0.3): (0.5~1), for example, 1: (1~1.5): (0.08~0.15): (0.6~0.8), and exemplarily 1:1: 0.08: 0.8.
[0016] According to an embodiment of the present invention, the raw material in step (1) further comprises water. Furthermore, the mass ratio of the water to the first monomer is 1:(0.15-0.3).
[0017] According to an embodiment of the present invention, the first monomer is added in the form of an aqueous solution, and the concentration of the first monomer is, for example, 10-50 wt %, and exemplarily 20 wt %.
[0018] In some embodiments, in step (1), the first monomer aqueous solution accounts for 40% to 70% by weight of the total mass of the adhesive surface preparation system, the acrylic acid accounts for 15% to 40% by weight of the total mass of the adhesive surface preparation system, the N-isopropylacrylamide accounts for 5% to 15% by weight of the total mass of the adhesive surface preparation system, and the photoinitiator accounts for 0.5% to 1% by weight of the total mass of the adhesive surface preparation system.
[0019] According to an embodiment of the present invention, the preparation in step (1) is polymerized under ultraviolet light (350-405 nm), for example, the intensity of the ultraviolet light is 50-200 mW / cm 2 .
[0020] According to an embodiment of the present invention, step (1) comprises: firstly mixing a first monomer, a second monomer, N-isopropylacrylamide (NIPAM), a photoinitiator and water, and obtaining a prepolymer solution after deoxygenation and degassing; and polymerizing the prepolymer solution under ultraviolet light to obtain a hydrogel having adhesion on both sides.
[0021] According to an embodiment of the present invention, the raw material in step (2) further includes water; further, the mass ratio of the water to the third monomer is 1: (0.5~1).
[0022] According to some embodiments of the present invention, in step (2), the mass content of the third monomer solution is 40% to 80 wt%, and / or the content of the photoinitiator is 0.5% to 1 wt% of the total mass of the third monomer.
[0023] According to an embodiment of the present invention, the preparation in step (2) is polymerized under ultraviolet light (350-405 nm), for example, the intensity of the ultraviolet light is 50-200 mW / cm 2 .
[0024] According to some embodiments of the present invention, step (2) comprises: mixing a third monomer, a photoinitiator and water, immersing the single adhesive surface of the hydrogel obtained in step (1) in the mixed solution, standing for at least 10 minutes, and reacting under ultraviolet light to obtain the Janus hydrogel.
[0025] According to an exemplary embodiment of the present invention, the method for preparing the Janus hydrogel comprises the following steps: (S1) mixing polyethyleneimine / hyperbranched polyethyleneimine (PEI), acrylic acid (AA), N-isopropylacrylamide (NIPAM) and a photoinitiator in deionized water and stirring to form a mixed solution; (S2) introducing nitrogen or an inert gas into the mixed solution to deoxygenate the mixed solution, and removing bubbles in the mixed solution by ultrasound to obtain a prepolymer solution; (S3) uniformly injecting the prepolymerized liquid into a polytetrafluoroethylene mold and polymerizing it under ultraviolet light for 10 min to obtain a hydrogel having adhesion on both sides; (S4) Soaking one side of the hydrogel having adhesive properties on both sides in an aqueous solution containing a photoinitiator and DMAPS and leaving it to stand for 10 to 30 minutes; reacting it under ultraviolet light for 5 minutes, and then rinsing it with deionized water to obtain a Janus hydrogel.
[0026] The present invention also provides the use of the above-mentioned Janus hydrogel as a medical adhesive material; preferably, as a wet tissue surface adhesive material. In some embodiments, the Janus hydrogel is used as a dura mater repair material.
[0027] According to an embodiment of the present invention, the wet tissue includes but is not limited to intestine, liver, spleen, lung, heart, stomach, kidney, dura mater and the like.
[0028] In this application, "Janus supramolecular hydrogel" and "Janus hydrogel" have the same meaning.
[0029] Beneficial Effects The present invention provides a novel "two-faced" Janus supramolecular hydrogel, which has an integrated structure and asymmetric adhesion function: on one side, reversible adhesion is generated through N-isopropylacrylamide and a first monomer and a second monomer, and the hydrogel can effectively adhere to a wet tissue surface (for example, to block cerebrospinal fluid leakage); on the other side, zwitterionic monomers are introduced into the hydrogel through single-sided solvent induction, and an anti-adhesion layer is formed after polymerization, which can prevent tissue adhesion and protein adhesion. Since the zwitterionic anti-adhesion layer and the monomer (polyethyleneimine, polyacrylic acid) components in the adhesion layer produce strong ionic interactions, a firm and dense bond is produced, rather than the simple splicing and compounding of traditional hydrogels.
[0030] In addition, the Janus supramolecular hydrogel also has the following advantages: (1) No cross-linking agent is used, which is beneficial to improve the safety of the material and has good biocompatibility; (2) Extremely low swelling rate (<2%); (3) good mechanical properties (elongation at break of 600%, tensile breaking strength of more than 2 MPa, adhesion strength to wet tissues such as pig skin of more than 70 kPa), self-repairing and extracellular matrix-like dynamic viscoelasticity; (4) Temperature responsiveness and relaxation facilitate adaptation to in vivo tissues, resulting in better mechanical matching and enhanced adhesion; (5) The preparation process is simple and easy, the material price is low, and it is easy to manufacture on a large scale, which has great application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 :Swelling rate, tensile strength and tensile fracture strength of Janus supramolecular hydrogel; Figure 2 :Tensile strength and cyclic tensile strength diagram of Janus supramolecular hydrogel; Figure 3 :Rheological behavior diagram of Janus supramolecular hydrogel; Figure 4 :Thermoresponsiveness diagram of Janus supramolecular hydrogel; Figure 5 :Morphological characterization of Janus supramolecular hydrogel; Figure 6 :Anti-protein adhesion diagram of both sides of Janus supramolecular hydrogel; Figure 7 : Cytocompatibility of Janus supramolecular hydrogel (control group is cell culture dish) and Masson staining of tissue sections 14 days after implantation in rats (dura mater); Figure 8 :The adhesion of Janus supramolecular hydrogel to various tissues is shown; Fig. 9 :Adhesion diagram of two sides of Janus supramolecular hydrogel; Fig.10 :A diagram showing the sealing ability of Janus supramolecular hydrogel on tissues in a wet environment. DETAILED DESCRIPTION
[0032] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0033] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0034] Example 1
[0035] A self-adaptive Janus supramolecular hydrogel and its preparation method and application (1) Weigh 6 g of polyethyleneimine (Mn = ~70000) aqueous solution (20 wt%), 4 g of acrylic acid, 0.5 g of N-isopropylacrylamide, and 20 µL of photoinitiator 2,2-diethoxyacetophenone (DEAP), add 1 mL of deionized water and stir thoroughly for 10 minutes to dissolve. Finally, use an ultrasonic cleaner for 5 minutes to remove bubbles in the mixed solution. (2) Add the mixed solution obtained in step 1 dropwise into the polytetrafluoroethylene mold and irradiate it with a UV lamp with a wavelength of 365 nm (power of 160 W) for 600 s. Then, gently take out the hydrogel sample and rinse it three times with saline for later use; (3) Accurately weigh 5 g of zwitterionic monomer [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (DMAPS), add 5 g of deionized water and 50 µL of photoinitiator 2,2-diethoxyacetophenone (DEAP), stir thoroughly and remove bubbles in the mixture using an ultrasonic cleaner; (4) Place the hydrogel prepared in step (2) on a fixture so that one side of the hydrogel is immersed in the mixed solution prepared in step (3). After immersion for 20 minutes, remove the hydrogel and irradiate the side of the hydrogel immersed in DMAPS with an ultraviolet lamp with a wavelength of 365 nm (power of 160 W) for 600 s. Rinse three times with saline to obtain the Janus supramolecular hydrogel.
[0036] The present embodiment is based on polyethyleneimine, acrylic acid, N-isopropylacrylamide and zwitterionic monomer DMAPS to construct Janus supramolecular hydrogel adhesive with different adhesion on both sides. PEI, AA and NIPAM produce dynamic viscoelasticity similar to extracellular matrix through hydrogen bonds, ionic bonds and hydrophobic interactions, with extremely low swelling rate, good mechanical stability, tissue compatibility, and can be firmly adhered to wet tissue surface; the carboxyl group of polyacrylic acid and the positive charge of polyethyleneimine can form a large number of hydrogen bonds and ion complexes with the surface of various substrates, giving hydrogel adhesion, and copolymerizing with PNIPAM reduces the phase transition temperature, and has good flexibility and mobility after the hydrogen bonds between polymer chains are broken at 37 ° C in vivo, which is conducive to hydrophobic aggregation, and further removes the interfacial water of tissue and gel to enhance adhesion performance. By soaking the zwitterionic monomer solution on one side, the adhesion layer is firmly combined through strong ionic interactions and then polymerized, and finally a Janus hydrogel patch with different adhesion on both sides is constructed.
[0037] Figure 1 The swelling rate, tensile strength and tensile fracture strength test results of Janus hydrogel are shown in Figure 2. The hydrogel was immersed in deionized water for 10 days, and the mass and volume changes of the hydrogel were tested every day and the swelling rate was calculated. The swelling rate was found to be less than 2%. The hydrogel was immersed in deionized water for equilibrium and then cut into samples with a length of 50 cm, a width of 20 mm and a thickness of 1 mm. The samples were tensile tested using a universal testing machine at a speed of 10 mm / min. The elongation at break was found to be 600% and the tensile fracture strength exceeded 2 MPa.
[0038] Figure 2 The strength of Janus hydrogel at different stretch lengths and its cyclic test at 400% stretch length were tested under the same test conditions. Figure 1 The above shows that the hydrogel has excellent flexibility and still maintains high mechanical properties after undergoing 10 times of 4-fold stretching.
[0039] Figure 3 For the rheological test of Janus hydrogel, the hydrogel was immersed in deionized water for equilibrium and then cut into discs with a thickness of 2 mm and a diameter of 2 cm. The storage modulus and loss modulus of the hydrogel were tested using an Anton Paar rotational rheometer, and the viscoelasticity and self-healing properties of the hydrogel were studied by changing the shear deformation size. Figure 4 In order to study the effect of the modulus of Janus hydrogel by changing different test temperatures, it was proved that the hydrogel is temperature responsive.
[0040] Figure 5The SEM image of the hydrogel is shown in Figure 1. The prepared hydrogel was frozen at -20°C and broken with liquid nitrogen, then placed in a freeze dryer for 72 hours, and then the sample was sprayed with gold and the surface morphology was observed using a SEM. From the image, it can be seen that the adhesion surface and the anti-adhesion surface have different morphologies. The anti-adhesion surface is a smooth and dense structure, while the adhesion surface has a porous structure, which is conducive to the growth of cells.
[0041] Figure 6 To demonstrate the anti-protein adhesion performance of commercial bovine pericardial patch, gelatin sponge and Janus hydrogel, fluorescein isothiocyanate-labeled bovine serum albumin (BSA-FITC) and each material were co-cultured at 37°C for 4 h, rinsed with saline three times, and the protein adhesion on the material surface was photographed using a laser confocal microscope. The amount of bovine serum albumin on the material surface was determined using a BCA kit, and the results showed that the anti-adhesion layer of the Janus hydrogel material had excellent anti-protein adhesion performance.
[0042] Figure 7 The cell proliferation after 1, 3, and 5 days of co-culture of Janus hydrogel material and fibroblast NIT3T3 (upper figure) and tissue section staining after 14 days of implantation of the hydrogel patch into male SD rats (at the dura mater) (lower figure). Cell viability was quantitatively analyzed using the CCK8 kit, and tissue section staining was performed by Masson staining to observe its morphology and inflammation. The results demonstrated that the hydrogel has good biocompatibility both in vivo and in vitro.
[0043] Figure 8 The adhesion of Janus hydrogel materials to various tissues including heart, liver, spleen, lung, kidney, stomach, pig skin and various engineering materials (glass, stainless steel, PVC, PDMS and Ti) was demonstrated, proving that the hydrogel has a wide range of adhesion.
[0044] Fig. 9 The adhesion strength of both sides of Janus hydrogel to the skin, heart, liver, spleen, lung, kidney, and stomach tissues showed that the hydrogel adhesion layer had excellent adhesion strength, while the anti-adhesion layer showed extremely low adhesion strength. It can be considered that the anti-adhesion layer has the property of preventing tissue adhesion.
[0045] Fig.10 The adhesive layer of Janus hydrogel was used to block the damaged gastric juice leakage of rabbits, and no leakage occurred after adhesion. The experimental results showed that the hydrogel can achieve instantaneous adhesion and block leakage, indicating its stable adhesion performance in a wet environment.
[0046] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Janus hydrogel, characterized in that The Janus hydrogel has an adhesive surface and an anti-adhesive surface; The adhesive surface is prepared from raw materials including a first monomer, a second monomer, N-isopropylacrylamide and a photoinitiator; The anti-adhesion surface is prepared from raw materials including a third monomer and a photoinitiator; The first monomer is selected from one or more of polyethyleneimine, hyperbranched polyethyleneimine, tetraethylenepentamine, triethylenetetramine, polylysine, polymethacrylate N,N-dimethylaminoethyl, polyethyleneamine and polypropyleneimine; The second monomer is selected from one or more of acrylic acid, methacrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, itaconic acid, vinyl phosphate, and hydroxyethyl phosphate methacrylate; The third monomer is a zwitterionic monomer; The raw materials for preparing the adhesive surface and the anti-adhesive surface do not contain toxic additives.
2. The Janus hydrogel according to claim 1, characterized in that The zwitterionic monomer includes, but is not limited to, one or more of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate.
3. The Janus hydrogel according to claim 1, characterized in that The molecular weight of the first monomer is 30,000-100,000.
4. The Janus hydrogel according to claim 1, characterized in that The Janus hydrogel has an integrated structure, that is, the adhesion surface and the anti-adhesion surface form an interpenetrating network structure and generate a strong interface bond through strong ionic interaction.
5. The Janus hydrogel according to claim 1, characterized in that The photoinitiator is selected from α One or more of ketoglutaric acid, 2,2-diethoxyacetophenone and lithium phenyl (2,4,6-trimethylbenzoyl) phosphate.
6. The method for preparing the Janus hydrogel according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) preparing an adhesive surface from raw materials including a first monomer, a second monomer, N-isopropylacrylamide and a photoinitiator; (2) On one side of the adhesive surface, an anti-adhesive surface is prepared using a raw material including a third monomer and a photoinitiator to obtain the Janus hydrogel.
7. The preparation method according to claim 6, characterized in that The molar ratio of the first monomer, the second monomer, N-isopropylacrylamide and the third monomer is 1: (0.8-2): (0.05-0.3): (0.5-1), and the first monomer is calculated based on the molar amount of its structural unit.
8. The preparation method according to claim 6, characterized in that: The raw materials in step (1) also include water; In step (1), the first monomer aqueous solution accounts for 40-70 wt% of the total mass of the adhesive surface preparation system, the acrylic acid accounts for 15%-40 wt% of the total mass of the adhesive surface preparation system, the N-isopropylacrylamide accounts for 5%-15 wt% of the total mass of the adhesive surface preparation system, and the photoinitiator accounts for 0.5%-1 wt% of the total mass of the adhesive surface preparation system; And / or, the preparation in step (1) is polymerized under ultraviolet light.
9. The preparation method according to claim 6, characterized in that: The raw materials in step (2) also include water; In step (2), the mass content of the third monomer solution is 40% to 80wt%, and / or the content of the photoinitiator is 0.5% to 1wt% of the total mass of the third monomer; And / or, the preparation in step (2) is polymerized under ultraviolet light.
10. Use of the Janus hydrogel according to any one of claims 1 to 5 in the preparation of medical adhesive materials; The medical adhesive material is a wet tissue surface adhesive material, and the wet tissue includes but is not limited to intestines, liver, spleen, lungs, heart, stomach, kidneys, and dura mater.
Citation Information
Patent Citations
Janus hydrogel adhesive as well as preparation method and application thereof
CN113577370A
Janus hydrogel dressing for postoperative adhesion prevention and preparation method thereof
CN117414464A
Janus hydrogel with anti-inflammatory, antibacterial and asymmetric adhesion properties as well as preparation method and application of Janus hydrogel
CN118530410A
Temperature-sensitive debonding wet tissue adhesion hydrogel and preparation method thereof
CN114644766A
Janus zwitterionic hydrogel anti-adhesion membrane as well as preparation method and application thereof
CN116688247A
Cited By
3D printing high-strength supramolecular hydrogel and application thereof in bone defect repair
CN121059891A
Marine antifouling conductive hydrogel as well as preparation method and application thereof
CN121824995A
A marine antifouling conductive hydrogel, its preparation method and application
CN121824995B